PENGARUH JUMLAH MATA TUNAS TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS JAHE (ZINGIBER OFFICINALE L.) - Sri Redjeki Agustinah (JURNAL ILMIAH AGRINECA)
The objective of the research was to assess the effect of amount of bud to growth and yield some varieties of ginger. This field experiment was at Mojosongo, Boyolali and was arranged in split plot design based on randomized. Black design involving two factors and three replications. The result of the research concluded that: treatment of amount of bud and some varieties have significant effect to all growth and yield parameters. Interaction between of bud amount and some varieties have significant effect to weight rhizome per crop and rhizome per plot, but significant effect, fresh weight of crown per plant and dry weight of crown per plant. The emprit variety is the highest by amount of 3 bud (T2) (2,16 kg) plot; 4,82 ton (ha), merah variety is the highest by amount of 3 bud (2,92 kg) plot, 8,68 ton/ha, Gajah variety is the highest by amount of 4 bud to 3,22 kg/plot (9,58 ton/ha). Key word; Amount bud, ginger varieties